Positive psychological capital, entrepreneurial knowledge transfer, and entrepreneurial mindset growth: a synthesis of MSMEs’ challenges - Basri Bado; Thamrin Tahir; Muhammad Ilyas Thamrin Tahir; Muhammad Hasan (Cogent Business & Management)
MSMEs entrepreneurship is a central issue that is very important for the economic development of maritime countries, including in the marine and fisheries economic sector. When associated with the development of MSMEs in the economic development of the marine and fisheries sector, the development of human resources from the perspective of MSMEs entrepreneurship is one of the efforts that is prioritized. This study aims to investigate the role of positive psychological capital on entrepreneurial mindset growth through the mediation of entrepreneurial knowledge transfer. The sample in this study was 600 seaweed MSMEs actors. Data were collected through questionnaires and analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS) through SmartPls (version 4.0). This study successfully proved that positive psychological capital influences entrepreneurial mindset growth through the mediation of entrepreneurial knowledge transfer. These findings provide implications for the need to improve non-formal and informal entrepreneurship education programs with a focus on knowledge transfer between business actors, intermediary organizations, and research institutions through training, mentoring, and business networks.